2015
DOI: 10.1002/cphc.201500271
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Fluorescent Dyes Attached to G‐Quadruplex DNA and their Effect on FRET Experiments

Abstract: FRET spectroscopy is a promising approach for investigating the dynamics of G-quadruplex DNA folds and improving the targeting of G-quadruplexes by potential anticancer compounds. To better interpret such experiments, classical and replica-exchange molecular dynamics simulations and fluorescence-lifetime measurements are used to understand the behavior of a range of Cy3-based dyes attached to the 3' end of G-quadruplex DNA. The simulations revealed that the dyes interact extensively with the G-quadruplex. Iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Interestingly, this study did not show a significant change in the melting temperature of hGQ in 100 mM NaCl with or without Cy5 at the end of GQ. More recently, molecular dynamics simulations have shown that a Cy3 molecule that is attached to the 3' end of hGQ with a six-carbon N-hydroxysuccinimide (NHS) linker attached to a primary amine, significantly interacts with the GQ (Sondergaard et al 2015). Fluorescence lifetime measurements on this construct have shown that these interactions result in a significant shift in fluorescence lifetime compared to a free dye not attached to DNA (Sondergaard et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this study did not show a significant change in the melting temperature of hGQ in 100 mM NaCl with or without Cy5 at the end of GQ. More recently, molecular dynamics simulations have shown that a Cy3 molecule that is attached to the 3' end of hGQ with a six-carbon N-hydroxysuccinimide (NHS) linker attached to a primary amine, significantly interacts with the GQ (Sondergaard et al 2015). Fluorescence lifetime measurements on this construct have shown that these interactions result in a significant shift in fluorescence lifetime compared to a free dye not attached to DNA (Sondergaard et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, molecular dynamics simulations have shown that a Cy3 molecule that is attached to the 3' end of hGQ with a six-carbon N-hydroxysuccinimide (NHS) linker attached to a primary amine, significantly interacts with the GQ (Sondergaard et al 2015). Fluorescence lifetime measurements on this construct have shown that these interactions result in a significant shift in fluorescence lifetime compared to a free dye not attached to DNA (Sondergaard et al 2015). In these measurements, the free dye exhibited a mono-exponential decay with a lifetime of 207±2 ps, while the dye attached to the end of GQ showed a multi-exponential decay with an additional ≈2 ns decay component.…”
Section: Resultsmentioning
confidence: 99%
“…MD simulations have proven to be very useful in generating possible conformations of the system that help interpreting observed efficiencies in terms of well‐defined D / A separations and orientations . As it will be discussed in the following sections, MD simulations also allow investigating the interplay between EET and structural dynamics by properly postprocessing trajectories of electronic coupling values, thus allowing to generate the expected FRET observables in intermediate situations between the limiting dynamic and static averaging regimes.…”
Section: Förster Expression Of the Eet Ratementioning
confidence: 99%
“…74,110 The time-domain approach is useful to recover some of the approximations made in the derivation of the FCWD term. For example, if the modes of A and D are not independent, a new term g AD (t), that accounts for correlated energy fluctuations, appears in the exponent of Equation (33). In this condition, the FCWD term cannot be expressed as spectral overlap (see Equation (28)), because now the integrand in the time domain cannot be factorized.…”
Section: Spectral Density (Sd) and Time-domain Formulation Of The Ementioning
confidence: 99%
See 1 more Smart Citation